The role of nutrigenetics in diet personalisation - Rogulska, Karolina; Strońska, Aleksandra; Grzeszczak, Konrad (Journal of Education, Health and Sport, 2021)
Nutrigenetics is the field that studies genetic differences in relation to food components. It also examines the risk of food-dependent diseases. The search for genes responsible for disease occurrence is very difficult because the human genome has about 25,000 genes. Association studies are used to identify the relevant genes, and then the presence of polymorphisms is compared with a group of healthy people (control group). Thanks to these tests, it is possible to take an individual approach to the patient and arrange a personalized diet, which results in obtaining the best results. This article focuses on selected diseases including lactase deficiency, celiac disease, phenylketonuria and folate deficiency. In each of these diseases thanks to molecular research, it is possible to detect genetic defects, and then to apply a personalized diet which excludes or provides certain food products. Further development of nutrigenetics in the future will allow even better selection of diets in other disease entities.